Marshalling McLuhan’s Tetrad in Soundscape Composition: A Focus-Group Approach to Music-Based Research - Azzano, Maurice (New Explorations)

(untitled) (New Explorations Association, 2024)
This study was conducted to examine novel ways that soundscape composition may inform a specific community from an acoustic perspective. The purpose of this paper is four-fold: 1) to explore qualitatively ways that soundscape composition can extend knowledge through a music-based approach to research; 2) to expand the definition of an acoustic community; 3) to provide strategies for implementing Marshall McLuhan’s model of the Tetrad (his Laws of Media) in phenomenological inquiry; and 4) to examine alternative strategies for music-based research.